Prospective and retrospective memory are differentially related to self-rated omission and commission errors in medication adherence in multimorbidity. Issue 6 (2nd November 2017) - Ihle, Andreas; Inauen, Jennifer; Scholz, Urte; König, Claudia; Holzer, Barbara; Zimmerli, Lukas; Battegay, Edouard; Tobias, Robert; Kliegel, Matthias
ABSTRACT: We investigated the relations of self-rated omission errors (i.e., forgetting to take one's medication) and commission errors (i.e., unnecessary repetitions of medication intake because of forgetting that it has already been taken) in medication adherence in multimorbidity to prospective and retrospective memory performance. Moreover, we examined whether these relations were moderated by the number of medications that had to be taken. Eighty-four patients with multimorbidity (aged 28–84 years, M  = 62.4) reported medication adherence regarding the last seven days and the number of medications they had to take. In addition, we administered psychometric tests on prospective memory (PM) and retrospective memory performance. We found that reported omission errors in medication adherence were related significantly to lower PM performance. This relationship was increased in individuals with a lower number of medications. In comparison, reported commission errors in medication adherence were related significantly to lower retrospective memory performance. This relationship was increased in individuals with a larger number of medications. Present data suggest that omission errors in medication adherence in multimorbidity may reflect primarily PM errors, particularly if few medications have to be taken, while commission errors may reflect mainly retrospective memory failures, especially with a large number of medications that need to be taken as prescribed. From an applied neuropsychological perspective, these results underline the importance of trying to enhance PM and retrospective memory performance in patients with multimorbidity.